Step by step : tubo uterine factors in infertility - Ghumman, Surveen (Jaypee, 2007)
The book attempts to roadmap the latest therapies, defining their current relevance to diagnosis and treatment, in a simplified, easy to follow protocol for the practicing infertility specialist with flow charts for management providing guidance in a step by step manner. At the same time besides giving practical guidance, it also touches on the latest research work done in the field. A comprehensive classification, investigation and management of all tubo-uterine factors causing infertility have been presented in the book and the accompanying DVD-ROM. The DVD-ROM shows among others, the technique of endoscopic management of endometrioma, ectopic pregnancy, myoma, intrauterine adhesions, tubal and peritubal pathologies. This book has been written with the aim of placing the modern approach to the management of infertility in the context of sound theory. evidence based therapy and recent advances. In this day of information overload this book is and attempt to integrate information into a practice management protocol that is rational, logical and rewarding for the reader.